Cannulated Screw Prominence in Tension Band Wiring of Patella Fractures Increases Fracture Gapping: A Cadaver Study. Issue 5 (May 2019) - Avery, Matthew C.; Jo, Sally; Chang, Andrew; Ricci, William M.; McAndrew, Christopher; Miller, Anna N.; Tang, Simon
Abstract: Background: Transverse patella fractures are often treated with cannulated screws and a figure-of-eight anterior tension band. A common teaching regarding this construct is to recess the screws so that their distal ends do not protrude beyond the patella because doing so may improve biomechanical performance. However, there is a lack of biomechanical or clinical data to support this recommendation. Question: In the treatment of transverse patella fractures, is there a difference between prominent and recessed cannulated screw constructs, supplemented by tension banding, in terms of gap formation from cyclic loading and ultimate load to failure? Methods: Ten pairs of fresh-frozen cadaver legs (mean donor age, 72 years; range, 64–89 years) were randomized in a pairwise fashion to prominent or standard-length screws. In the prominent screw group, screw length was 15% longer than the measured trajectory, resulting in 4 to 6 mm of additional length. Each patella was transversely osteotomized at its midportion and fixed with screws and an anterior tension band. Gap formation was measured over 40 loaded flexion-extension cycles (90° to 5°). Ultimate load to failure was assessed with a final monotonic test after cyclic loading. Areal bone mineral density (BMD) of each patella was measured with dual energy x-ray absorptiometry (DEXA). There was no difference in BMD between the recessed (1.06 ± 0.262 g/cm 2 ) and prominent (1.03 ± 0.197 g/cm 2 ) screw groups (p = 0.846). Difference in gap formation was assessed with a Wilcoxon Rank Sum Test. Ultimate load to failure and BMD were assessed with a paired t-test. Results: Patella fractures fixed with prominent cannulated screws demonstrated larger gap formation during cyclic loading. Median gap size at the end of cyclic loading was 0.13 mm (range, 0.00–2.92 mm) for the recessed screw group and 0.77 mm (range, 0.00–7.50 mm) for the prominent screw group (p = 0.039; 95% confidence interval [CI] difference of geometric means, 0.05–2.12 mm). There was no difference in ultimate failure load between the recessed screw (891 ± 258 N) and prominent screw (928 ± 268 N) groups (p = 0.751; 95% CI difference of means, -226 to 301 N). Ultimate failure load was correlated with areal BMD (r = 0.468; p = 0.046). Conclusions: In this cadaver study, when using cannulated screws and a figure-of-eight tension band to fix transverse patella fractures, prominent screws reduced the construct's ability to resist gap formation during cyclic loading testing. Clinical Relevance: This biomechanical cadaver study found that the use of prominent cannulated screws for the fixation of transverse patella fractures increases the likelihood of interfragmentary gap formation, which may potentially increase the risk of fracture nonunion and implant failure. These findings suggest that proximally and distally recessed screws may increase construct stability, which may increase the potential for bony healing. The findings support further laboratory and clinical investigations comparing recessed screws supplemented by anterior tension banding with other repair methods that are in common use, such as transosseous suture repair.